Investigation of Antimicrobial Activities and Molecular Docking Studies of Synthesized Sulfonamide Compounds - Ozbey, G.; Tanriverdi, E. S.; Senkal, B. F.; Korkmaz, B.; Erkan, S.; Bulut, N.; Otlu, B. (Springer, 2023)
Sulfonamides are commonly used worldwide. In this study, several sulfonamide compounds such as N-(4-acetylphenyl)-4-methylbenzenesulfonamide (PSASF), N-(3-acetylphenyl)-4-methylbenzenesulfonamide (PSASF-1), 1-tosyl-1H-imidazole (PSASF-x), 4-methyl-N-(pyridin-4-yl) benzenesulfonamide (PSASF-2), and 1-ethyl-4-tosylpiperazine (PSASF-3) have been synthesized, with antibacterial activities against Escherichia coli ATCC 25922, Pseudomonas aeruginosa ATCC 27853, and Staphylococcus aureus ATCC 29213 have been evaluated. Antibacterial properties of drugs were studied in depth using molecular docking research. In addition, the synthesized compounds were characterized using spectral analysis. Antibacterial activities of synthesized derivates were determined against E. coli, P. aeruginosa, and S. aureus with minimum inhibitory concentration (MIC) by using the broth microdilution method. All prepared compounds exhibited significant antibacterial activity against S. aureus, E. coli, and P. aeruginosa. The MIC value for E. coli and P. aeruginosa was determined as 256 mu g/mL. MIC against S. aureus was observed to be 256 and 512 mu g/mL for the PSASF compound and the other compounds respectively. Results of the current study revealed that four of the five compounds had weaker antibacterial activity against S. aureus at a concentration of 512 mu g/mL. However, the MIC values from our experiments are significantly higher in comparison with the reference drugs such as amoxicillin, ciprofloxacin, meropenem, and vancomycin in E. coli and S. aureus. On the other hand, in a comparison of the synthesized compounds with reference drugs in P. aeruginosa, no statistical difference was demonstrated. Antibacterial activity of the produced derivates was likewise an agreement with regard to the molecular docking and the laboratory results.
Keywords: antibacterial activity; MIC; molecular docking; sulfonamide; synthesis